EXTENT TO WHICH CLASSROOM PLAY INFLUENCE SOCIAL INTERACTIONS OF CHILDREN IN PUBLIC PRE-SCHOOLS IN RACHUONYO NORTH SUB-COUNTY, HOMABAY COUNTY, KENYA - Jane A. Omullo; Simon Nyakwara (IJRDO- Journal of Educational Research, 2020)
Play is a crucial part of any child’s social behavior and development. It helps children develop self-determination, self-control, and identity. These skills are primarily learned through interactions with other children. Specifically, the study focused on the extent to which classroom play influence social interactions of children in public pre-schools in Rachuonyo North Sub-County, Homabay County, Kenya. The information provided by this research will benefit policymakers, community members and academicians. It adopted a descriptive survey research design, with a target population of 492 persons. The sample size of 217 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analyzed for the two scores and found to be 0.78, thus, the instruments were reliable. Quantitative data was analyzed using descriptive statistics, and presented in tables. The study established that classroom play, playground play and field trip play had a statistically significant association with social interactions of children in public pre-schools.